Biological therapies for eosinophilic asthma. (3rd July 2018) - Patel, Shiven S.; Casale, Thomas B.; Cardet, Juan Carlos
ABSTRACT: Introduction : Severe uncontrolled asthma is by definition refractory to traditional therapies or can be controlled only with therapies that have intolerable side effects. Monoclonal antibodies that target interleukin (IL)-5/IL-5Rα, IgE, and IL-4Rα have shown favorable results in clinical trials, including reductions in asthma exacerbations and other important clinical outcomes. These biological agents offer treatment alternatives to patients with uncontrolled severe eosinophilic asthma. Areas covered : This article reviews how the shifting emphasis toward identifying distinct asthma phenotypes has led to the approval of biological therapies that preferentially benefit patients with severe eosinophilic asthma. The clinical trials that led to the approval of these biologic treatments are discussed in detail. Expert opinion : Biologic therapies targeting the IL-5, IgE, IL-4/IL-13 signaling pathways have been successful in clinical trials in subjects with severe eosinophilic asthma. Some of these agents have also been successful regardless of peripheral blood eosinophil counts. These treatments have shown a relatively favorable safety profile in clinical trials, although long-term safety data for some of these agents are limited. Due to the high costs associated with these medications, they should be reserved for select patients where they yield a therapeutic and pharmacoeconomic advantage.